2023
DOI: 10.1093/humupd/dmad030
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in pregnant women: a systematic review and meta-analysis on the risk and prevalence of pregnancy loss

Janneke A C van Baar,
Elena B Kostova,
John Allotey
et al.

Abstract: BACKGROUND Pregnant women infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are more likely to experience preterm birth and their neonates are more likely to be stillborn or admitted to a neonatal unit. The World Health Organization declared in May 2023 an end to the coronavirus disease 2019 (COVID-19) pandemic as a global health emergency. However, pregnant women are still becoming infected with SARS-CoV-2 and there is limited information available regarding the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 146 publications
0
1
0
Order By: Relevance
“…First and second trimester infections did not cause any adverse pregnancy outcomes when compared to noninfected controls 15,24,25 . Large cohort studies also found that the risks of stillbirth or neonatal death were not signi cantly increased, regardless of symptom status 26,27 Research of 68 stillbirths found that only 2 cases of fetal infection were con rmed, indicating that SARS-CoV-2 was not involved in the cause of fetal or neonatal deaths 28 .…”
Section: Pregnancy Outcomesmentioning
confidence: 80%
“…First and second trimester infections did not cause any adverse pregnancy outcomes when compared to noninfected controls 15,24,25 . Large cohort studies also found that the risks of stillbirth or neonatal death were not signi cantly increased, regardless of symptom status 26,27 Research of 68 stillbirths found that only 2 cases of fetal infection were con rmed, indicating that SARS-CoV-2 was not involved in the cause of fetal or neonatal deaths 28 .…”
Section: Pregnancy Outcomesmentioning
confidence: 80%
“…However, depending on how studies are designed, it may not be possible to report outcomes across pregnancy trimester and after birth. This was evident during the COVID-19 pandemic where most studies covered late pregnancy and neonatal vital status, and few early pregnancy outcomes were covered [8,30]. Other examples of overlap include low or abnormal APGAR score, reporting of actual APGAR score values, and birth asphyxia; or size for gestational age, which requires for its computation data on gestational age and birthweight.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that vertical transmission from mother to child during pregnancy (i.e., transmission via placenta) is not supported by current data, but that vertical transmission at the time of delivery or breastfeeding can be exceptionally possible [ 23 ]. Other reviews have also been unable to identify any significant association between acute SARS-CoV-2 infection in early pregnancy (the first 20 weeks of gestation) and adverse fetal, neonatal or maternal outcomes [ 24 , 25 ]. Nevertheless, Rodriguez-Wallberg et al warned of a 44% increase in the rate of miscarriage rate in recent years [ 24 ].…”
mentioning
confidence: 99%